Working from home during the COVID-19 pandemic. The role of physical activity to counteract the workers’ oxidative stress. A pilot study - Federica Ghelli; Giulia Squillacioti; Valeria Bellisario; Samar El Sherbiny; Fulvia Guglieri; Giulia M. Picone; Roberto Bono (Digital Health, 2023)
Objective Office workers spend typically more than two-thirds of their working time sitting and this negative behaviour could have been increased during the pandemic. Low levels of Physical Activity (PA) can have detrimental effects on health, well-being, and Quality of Life (QoL), as well as on the oxidative stress burden. Our aim was to evaluate the role of moderate PA remotely administered in modulating the bio-molecular profile and the QoL of a group of workers during the COVID-19 pandemic. Methods The 26 subjects recruited were sampled at the beginning of the study (T0), after 3 months of remotely administered training (T1), and 3 months after the suspension of the online workouts (T2). Each of the three times, subjects filled out a questionnaire and provided a spot urine sample for the quantification of oxidative stress (15-F2t-Isoprostane, Thiobarbituric Acid Reactive Substances (TBARS), and Total Antioxidant Power (TAP)) and inflammatory biomarkers (Interleukin (IL)-6 and IL-10). Results The PA administration resulted in a significant decrease in 15-F2t-Isoprostane ( p  = 0.02) and TAP ( p  = 0.019). A significant increase in TAP was observed between T1 and T2 ( p  = 0.044). Conclusion A PA-based health promotion strategy could be a valuable intervention in the working environment to promote the well-being of an ageing workforce, especially for white collars.